Evaluating the European transportation sector via energy and climate change mitigation perspectives - Gokgoz, Fazil; Yalcin, Engin (Elsevier, 2025)
Transportation is essential to a country's economic growth. However, it is one of the most energy intensive processes, and its negative environmental consequences are expected to worsen with time. Without successful climate change mitigation measures, it is predicted that transportation's negative environmental consequences will worsen, accelerating global warming. Enhancing energy efficiency and fostering sustainable practices in transportation have become urgent priorities to mitigate climate change. It is essential to evaluate to what extent European Union (EU) countries perform efficiently in terms of transport sustainability. Hence, we use Multi-Criteria Decision Making (MCDM) and slack-based Data Envelopment Analysis (DEA) to evaluate the energy performance in the transportation sector in the EU. The study focuses on 2018-2019 period. The findings show that the strong GDP and highly developed transport infrastructure of Germany, France, and Italy continue to dominate the MCDM and DEA efficiency rankings. The analysis shows a huge efficiency gap between the best and worst performing EU countries both in 2018 and in 2019, which indicates remarkable differences in transport sector performance in the EU. Developing countries display high inefficiencies because of a higher rate of energy usage than required. Based on our findings, policy implications towards the integration of alternative energy, upgrading infrastructure, and effective transport management can bridge efficiency gaps in the EU. This study emphasizes the necessity of sustainability and climate change mitigation efforts to render the European transport sector more efficient and less harmful to the environment.
Keywords: Energy; Climate change mitigation; Multi-criteria decision making; Data envelopment analysis; European Union